Methadone safety: a clinical practice guideline from the american pain society and college on problems of drug dependence, in collaboration with the heart rhythm society. - Chou, Roger; Cruciani, Ricardo A; Fiellin, David A; Compton, Peggy; Farrar, John T; Haigney, Mark C; Inturrisi, Charles; Knight, John R; Otis-Green, Shirley; Marcus, Steven M; Mehta, Davendra; Meyer, Marjorie C; et al. (The journal of pain : official journal of the American Pain Society, 2014)
Methadone is used for the treatment of opioid addiction and for treatment of chronic pain. The safety of methadone has been called into question by data indicating a large increase in the number of methadone-associated overdose deaths in recent years that has occurred in parallel with a dramatic rise in the use of methadone for chronic pain. The American Pain Society and the College on Problems of Drug Dependence, in collaboration with the Heart Rhythm Society, commissioned an interdisciplinary expert panel to develop a clinical practice guideline on safer prescribing of methadone for treatment of opioid addiction and chronic pain. As part of the guideline development process, the American Pain Society commissioned a systematic review of various aspects related to safety of methadone. After a review of the available evidence, the expert panel concluded that measures can be taken to promote safer use of methadone. Specific recommendations include the need to educate and counsel patients on methadone safety, use of electrocardiography to identify persons at greater risk for methadone-associated arrhythmia, use of alternative opioids in patients at high risk of complications related to corrected electrocardiographic QTc interval prolongation, careful dose initiation and titration of methadone, and diligent monitoring and follow-up. Although these guidelines are based on a systematic review, the panel identified numerous research gaps, most recommendations were based on low-quality evidence, and no recommendations were based on high-quality evidence.